1999
DOI: 10.1063/1.478530
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser interactions with methyl iodide clusters. I. Coulomb explosion at 795 nm

Abstract: The study of the interaction of femtosecond laser radiation with matter, especially clusters, has blossomed in recent years due to advances in laser technology. One aspect of this interaction is Coulomb explosion. This effect occurs when the repulsive energy of like charges, known as Coulomb repulsion, overcomes the cluster’s total cohesive energy, causing the cluster to disintegrate into charged fragments. In this study, the interactions of methyl iodide clusters, formed in a supersonic expansion using argon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 75 publications
1
51
2
Order By: Relevance
“…Relatively little work has been reported on the interaction of intense laser light with molecular clusters [13,14,22] and it has relied exclusively on the application of onedimensional TOF methodology to clusters of modest size. The application of 2D-TOF methodology to atomic [2,19] and molecular clusters opens new vistas for such research; as the present results indicate, it also questions prevailing wisdom regarding cluster explosion dynamics.…”
Section: Coulomb Explosion Versus Hydrodynamic Expansionmentioning
confidence: 99%
“…Relatively little work has been reported on the interaction of intense laser light with molecular clusters [13,14,22] and it has relied exclusively on the application of onedimensional TOF methodology to clusters of modest size. The application of 2D-TOF methodology to atomic [2,19] and molecular clusters opens new vistas for such research; as the present results indicate, it also questions prevailing wisdom regarding cluster explosion dynamics.…”
Section: Coulomb Explosion Versus Hydrodynamic Expansionmentioning
confidence: 99%
“…Recently, the interaction of nanosecond laser with CH 3 I cluster was investigated widely, where multiply charged ions with high energy were observed experimentally [4][5][6][7]. Luo et al investigated the interaction of nanosecond laser with CH 3 I in diffused beam and pulsed beam by a time-of-flight mass spectrometer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Methyl iodide (CH 3 I) has been chosen in this experiment as it has been extensively studied in the past and is still the subject of many studies in recent years [18][19][20][21][22][23][24][25][26][27][28][29][30]. Recently, Graham et al [25] reported the study of the multielectron dissociative ionization (MEDI) processes induced by 50 fs strong laser at 10 16 W/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Lots of works about traditional MPI have been done under a laser intensity of 10 6 -10 9 W/cm 2 [19,21], and recent works about high intensity laser field and molecules were done under a laser intensity of 10 13 -10 17 W/cm 2 by picosecond and femtosecond lasers [25][26][27][28][29][30]. Recently, we reported the generation of C q+ (q = 2,3) in photoionization of benzene seeded in argon by 25 ns, 532 nm pulses from a YAG laser at intensity about 10 11 W/cm 2 [31].…”
Section: Introductionmentioning
confidence: 99%